2006
DOI: 10.1111/j.1600-6143.2006.01528.x
|View full text |Cite
|
Sign up to set email alerts
|

Living Donor Liver Transplantation for Biliary Atresia: A Single-Center Experience with First 100 Cases

Abstract: The aim of this study is to present our institutional experience in living donor liver transplantation (LDLT) as a treatment for end-stage liver disease in children with biliary atresia (BA). A retrospective review of transplant records was performed. One hundred BA patients (52 males and 48 females) underwent LDLT. The mean follow-up period was 85.5 months. The mean age was 2.4 years. The mean preoperative weight, height, and computed GFR were 12.2 kg, 82.5 cm, and 116.4 ml/min/1.73 m 2 , respectively. Twenty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
77
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(79 citation statements)
references
References 37 publications
2
77
0
Order By: Relevance
“…We have previously reported that the average change in core temperature during an LDLT for pediatric patients weighing less than 10 kg is significantly different from that in heavier children [5] . Furthermore, a lower survival rate for lower weight children was reported by Arnon et al [3] , and according to other studies, this poorer survival results from higher risks of perioperative vascular complications, bile duct complications and infections [4,6,7] . In pediatric kidney transplantation, the ideal body weight for a recipient has also been found to be greater than 10 kg [8] .…”
Section: Introductionmentioning
confidence: 97%
“…We have previously reported that the average change in core temperature during an LDLT for pediatric patients weighing less than 10 kg is significantly different from that in heavier children [5] . Furthermore, a lower survival rate for lower weight children was reported by Arnon et al [3] , and according to other studies, this poorer survival results from higher risks of perioperative vascular complications, bile duct complications and infections [4,6,7] . In pediatric kidney transplantation, the ideal body weight for a recipient has also been found to be greater than 10 kg [8] .…”
Section: Introductionmentioning
confidence: 97%
“…19 The donor and recipient evaluation and hepatectomies for liver transplant were performed as previously described. [20][21][22] There were no transplants that had ABO incompatibility. In all right lobe transplants, the grafts were excised without the middle hepatic vein.…”
Section: Evaluation and Proceduresmentioning
confidence: 99%
“…In Asia, living donor LT (LDLT) has been emerging as the solution of organ shortage to treat HCC. At Kaohsiung Chang Gung Memorial Hospital, the first case of LDLT was performed for a pediatric patient with biliary atresia in 1994, and progressed to adult LDLT in 1999 (3). In the high endemicity of hepatitis B and C (HBV and HCV), HCC has become the most indication for LT.…”
Section: Review Article On Liver Transplantation For Hepatocellular Cmentioning
confidence: 99%